Catheter fragment embolization: a rare yet serious complication of catheter use in pediatric oncology - Eryılmaz, Ertuğrul; Canpolat, Cengiz; Çeliker, Alpay (The Turkish Journal of Pediatrics, 2012)
Embolization is a rare but serious complication of venous central catheters in pediatric oncology. The reported cases in the literature are due in common to catheter ruptures. The most common cause is constant compression of the costoclavicular arch, known as "pinch-off" syndrome. We report a seven-year-old boy in whom embolization occurred as a late complication. Difficulty in the dissection of dense collagen periportal fibrosis was the main problem during the extraction session. The embolization occurred 10 months later. In an elective setting, percutaneous retrieval techniques were used successfully to extract the catheter fragments, and full recovery was achieved.